PENGARUH PROSES PENCAMPURAN TERHADAP SIFAT FISIK SEDIAAN VIRGIN COCONUT OIL(VCO) COLD CREAM - Octavianus Rico Aditya Putra; Agatha Budi Susiana Lestari (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2013)
Abstract The aim of the research was to investigate the significant effect among mixing time, mixing rate, and their interaction on the Virgin Coconut Oil (VCO) Cold Cream’s. In this research, the physical as properties of cold cream studied were viscosity, spreadability and viscosity shift. The result showed that mixing time, mixing rate and their interaction did not significantly affect the viscosity, spreadability, and viscosity shift responses.